Knowledge transfer among international strategic alliance partners and its impact on innovation performance. (25th September 2019) - Aggarwal, Vijita S.; Kapoor, Madhavi
The purpose of this study is to provide an overview of the literature available on knowledge transfer highlighting the factors affecting knowledge transfer mechanism and provides a theoretical framework to study its impact on strategic alliance's innovation performance. The paper studied a vast literature for providing a comprehensive framework to study the knowledge transfer mechanism among the alliance partners and its impact on performance. It also proposes a methodology for future empirical testing. The paper provides factors affecting knowledge transfer among international strategic alliance partners. A theoretical framework is prepared from the literature for further research integrating factors effecting knowledge transfer, linking them with innovation performance. This paper provides avenues for further research in the field of strategic management and international business for improving knowledge exchange for alliance's success. The paper could not review all the possible variables affecting knowledge transfer and is conceptual in nature. The paper provides a useful insight for managers involved in the international strategic alliances as well as for business executives for improving knowledge transfer mechanism among alliance partners. Although various researchers have studied knowledge transfer among international strategic alliances, not too many have linked factors affecting knowledge transfer with performance, which this study does.